2021
DOI: 10.1155/2021/7534601
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Molecular Basis of Nanocurcumin-Induced Telocyte Preservation within the Colon of Ulcerative Colitis Rat Model

Abstract: Background. Telocytes (TCs) are a distinct type of interstitial cells that play a vital role in the pathogenesis of ulcerative colitis and colonic tissue hemostasis. The aim of this study was to examine the effect of nanocurcumin (NC) on the morphometric and immunohistochemical characterization of TCs in the ulcerative colitis (UC) rat model. Methods. Forty rats were randomly divided into control, NC, UC, and UC+NC groups. At the end of the experiment, the colon was dissected and prepared for histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In recent years, with the development of industrialization, the incidence of UC has shown a significant upward trend in the world [ 21 ]. Although studies have shown that multiple factors such as genetics, immunity, environment, and intestinal microecology may lead to the occurrence of UC, the specific mechanism of UC is still unclear [ 22 , 23 ]. Due to the complexity of the pathogenesis of UC and the lack of specific biomarkers, it greatly increases the medical burden and physical and mental discomfort of patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of industrialization, the incidence of UC has shown a significant upward trend in the world [ 21 ]. Although studies have shown that multiple factors such as genetics, immunity, environment, and intestinal microecology may lead to the occurrence of UC, the specific mechanism of UC is still unclear [ 22 , 23 ]. Due to the complexity of the pathogenesis of UC and the lack of specific biomarkers, it greatly increases the medical burden and physical and mental discomfort of patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arafat et al [ 82 ] investigated the effects of nanoCUR (NC) on telocytes (TCs), interstitial cells that, in the colon, form the subepithelial reticular network, responsible for supporting the cells of the intestinal crypts and participating in tissue repair and regeneration processes. The analysis showed that the use of NC can be a therapeutic alternative for the treatment of UC since the compound proved to be efficient in inhibiting pro-inflammatory mediators, as well as favoring the maintenance of tissue architecture.…”
Section: Cur a Phenolic Compound Derived From Curcuma Longamentioning
confidence: 99%
“…Curcumin nanoparticles not only modulated the expression of the genes engaged in the inflammatory response in a rat model of UC; they also improved the mucosal lesions and preserved the distribution of telocytes, a distinct type of interstitial cells playing a vital role in colonic tissue homeostasis [ 70 ]. Interestingly, nanoparticles containing curcumin and catalase with poly(lactic-co-glycolic acid)-based surface functionalized with pluronic F127 enhanced mucus penetration and ROS-responsive drug release capacities for the delivery of curcumin to colitis tissues, thus resulting in more effective IBD therapy [ 71 ].…”
Section: Encapsulations Of Polyphenolic Compounds In Ibd and Crcmentioning
confidence: 99%